Legendary leadership - Garber, Peter R. (HRD Press, 2008)
Whether you are CEO of a large organization or president of the PTA, you're a leader and require the same qualities to be successful, according to Peter Garber. The information he presents in Legendary Leadership will help you become a good leader to those you lead and maybe even a legendary one. The book consists of four chapters full of information to help you make meeting the leadership challenge one of the most rewarding experiences in your life. You'll learn how your goal should be to earn the confidence of others, how to become a better leader by learning from the mistakes of others, how to handle your responsibilities and prioritize them correctly, why legendary leaders are remembered, what truly great leaders do that others do not, the importance of expanding your abilities as well as your perspective and much more. This book is part of the HR Skills Series designed to help managers plan for and manage changes in such areas as consumer demand, workforce turnover, and production and performance standards.
Print version record
Keywords: Leadership -- Study and teaching; Leadership; Étude et enseignement; BUSINESS & ECONOMICS; Workplace Culture; BUSINESS & ECONOMICS; Corporate Governance; BUSINESS & ECONOMICS; Leadership; BUSINESS & ECONOMICS; Organizational Development; Leadership; Study and teaching